APPLICATION OF DISASTER MITIGATION AT AN EARLY AGE IN THE COMMUNITY - Ernawati S K; Firdaus W Suhaeb (Universitas Negeri Makassar, 2024)
In an effort to reduce the risks and impacts that may arise due to disasters, effective mitigation measures are needed. It is important to spread understanding and skills in dealing with disaster threats to all levels of society. The study of the article aims to find out and describe the efforts to implement disaster mitigation at an early age in the community. By using the literature study method, the data obtained in this study is then compiled, analyzed, so as to obtain conclusions. The type of data, namely secondary data. The data collection technique, namely taking literature data, is then read, recorded, and processed from the study materials obtained. The results of the study show that disaster mitigation plays an important role in reducing the negative impact of disasters. These efforts are not only focused on post-disaster response, but also involve preventive, prepared, and risk reduction measures in the long term. The role of schools in disaster mitigation is very vital, where through disaster education in the school environment, students can increase knowledge, awareness, and preparedness in dealing with potential disaster threats. For this reason, disaster education that starts from an early age has a positive impact in forming a generation that is more concerned and ready to face potential disasters.